Factors influencing school readiness and behavioral problems of elementary students - Ng Hooi Yong; Melissa Ng Lee Yen Abdullah (Cakrawala Pendidikan: Jurnal Ilmiah Pendidikan)
Elementary Students experienced poor self-management and a lower level of school readiness. The purpose of the study is to identify the level of school readiness among elementary students with behavioral problems. It also aimed to identify the influences of self-regulation skills, parenting style, and transition support programs on school readiness and behavioral problems. The study involved 113 of 519 Year One student from six schools in the State of Perak, Malaysia, categorized as students with behavioral problems. The Year One Pupil's Readiness Instrument (IKMTS), Behavioral Problems Scale, Self-Regulation Scale, Parents Authority Scale, and Transition Activities Scale were utilized to collect the data for this study. Descriptive results showed that the level of school readiness among students with behavioral problems was moderate. Self-regulation skills and parenting style were revealed to be two major variables that impact school preparation and behavioral difficulties in the Partial Least Squares Structural Equation Modeling (PLS-SEM) study.